The role of gut microbiota in diarrhea and its alleviation through microbiota-targeted interventions - Tian, Rui; Chong, Chu-Jun; Bai, Ya-Ya; Chen, Ni; Qiao, Rui-Rui; Wang, Kan; Wang, Yu-Wei; Zhao, Peng; Zhao, Chong-Bo; Tang, Yu-Ping; Zhang, Li; Zhang, Qiao (Frontiers in Microbiology, 2025)
Diarrhea is a common gastrointestinal disease and closely related to the balance of the gut microbiota (GM). In turn, dysregulation of the GM can affect the onset and progression of diarrhea through regulating the metabolism, intestinal immune function, intestinal barrier function and changes in the brain-gut axis of host. Although increasing evidence suggests that GM is associated with gastrointestinal homeostasis and disease, the underlying mechanisms are not fully understood. GM disorder was often accompanied by diarrhea patients and animals, and the diarrhea caused by GM imbalance mainly involved the effects on short chain fatty acids (SCFAs), bile acids (BAs), intestinal barrier, immune system, and brain-gut microbiota axis (BGMA). In addition, intervening in the GM (probiotics, fecal microbiota transplantation and bacteriophage therapy) has been shown to be an effective way to alleviate diarrhea. In this review, the mechanism of diarrhea occurrence, probiotics, fecal microbiota transplantation and bacteriophage therapy intervene in diarrhea by regulating GM from basic and clinical research were summarized and discussed. We aim to provide the latest reference for studying the mechanism of treating diarrhea from the perspective of GM, and provide data support for clinical treatment of diarrhea.